Boosting the detection performance of severe acute respiratory syndrome coronavirus 2 test through a sensitive optical biosensor with new superior antibody - Lin, Chih‐Yen; Wang, Wen‐Hung; Li, Meng‐Chi; Lin, Yu‐Ting; Yang, Zih‐Syuan; Urbina, Aspiro Nayim; Assavalapsakul, Wanchai; Thitithanyanont, Arunee; Chen, Kai‐Ren; Kuo, Chien‐Cheng; Lin, Yu‐Xen; Hsiao, Hui‐Hua; et al. (Bioengineering & translational medicine, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus emerged in late 2019 leading to the COVID‐19 disease pandemic that triggered socioeconomic turmoil worldwide. A precise, prompt, and affordable diagnostic assay is essential for the detection of SARS‐CoV‐2 as well as its variants. Antibody against SARS‐CoV‐2 spike (S) protein was reported as a suitable strategy for therapy and diagnosis of COVID‐19. We, therefore, developed a quick and precise phase‐sensitive surface plasmon resonance (PS‐SPR) biosensor integrated with a novel generated anti‐S monoclonal antibody (S‐mAb). Our results indicated that the newly generated S‐mAb could detect the original SARS‐CoV‐2 strain along with its variants. In addition, a SARS‐CoV‐2 pseudovirus, which could be processed in BSL‐2 facility was generated for evaluation of sensitivity and specificity of the assays including PS‐SPR, homemade target‐captured ELISA, spike rapid antigen test (SRAT), and quantitative reverse transcription polymerase chain reaction (qRT‐PCR). Experimentally, PS‐SPR exerted high sensitivity to detect SARS‐CoV‐2 pseudovirus at 589 copies/ml, with 7‐fold and 70‐fold increase in sensitivity when compared with the two conventional immunoassays, including homemade target‐captured ELISA (4 × 10 3 copies/ml) and SRAT (4 × 10 4 copies/ml), using the identical antibody. Moreover, the PS‐SPR was applied in the measurement of mimic clinical samples containing the SARS‐CoV‐2 pseudovirus mixed with nasal mucosa. The detection limit of PS‐SPR is calculated to be 1725 copies/ml, which has higher accuracy than homemade target‐captured ELISA (4 × 10 4 copies/ml) and SRAT (4 × 10 5 copies/ml) and is comparable with qRT‐PCR (1250 copies/ml). Finally, the ability of PS‐SPR to detect SARS‐CoV‐2 in real clinical specimens was further demonstrated, and the assay time was less than 10 min. Taken together, our results indicate that this novel S‐mAb integrated into PS‐SPR biosensor demonstrates high sensitivity and is time‐saving in SARS‐CoV‐2 virus detection. This study suggests that incorporation of a high specific recognizer in SPR biosensor is an alternative strategy that could be applied in developing other emerging or re‐emerging pathogenic detection platforms.